THE PERSPECTIVES OF ADULT EDUCATION DEVELOPMENT IN THE CONTEXT OF LIFELONG LEARNING - Linkaitytė, Giedra Marija; Žilinskaitė, Lineta (Acta Paedagogica Vilnensia, 2008)
The idea of Lifelong learning was legalised for the countries of the European Union at the policy-making level when the Memorandum on Lifelong learning was published in 2000. This concept became the basis for reforming the educational system in many countries. The EU Communication, Adult Learning: It is never too late to learn!, adopted by the Commission in 2006, attests the relevancy of its implementation in adult education.Education theoreticians and politicians alike admit that the projects for implementing the Lifelong learning idea face difficulties. Theoreticians in adult education report that the road for implementing this idea – a change of paradigm from education to learning – raises problems even in those countries where adult education already has deep traditions. Research on implementations of Lisbon Strategy (2000), written at the request of politicians in 2004, revealed that the results anticipated by the Lisbon Strategy had not been warranted. Therefore, new directions of activities were foreseen. One of them was to make Lifelong learning a specific reality.Research object is the expression of the Lifelong learning (LLL hereafter) idea implementation in adult education. Research objective is to clarify the strategic directions for adult education in Lithuania in the context of European education forecasts. The article presents means for the establishing the characteristics of the LLL concept. Based on this concept, four categories were distinguished: the learner, social environment, lifelong education and expression of the LLL concept. In the first stage the analysis of contemporary situation in adult education was performed and the aspects of forecasting were clarified. In the second stage, by employing the means for the establishing the characteristics of the LLL concept, features of the vision and mission for LLL by the year 2012 were identified in the documents foreseeing its implementation. The analysis of documents forecasting the future of adult education contributed to the clarification of the perspective of a further vaision and mission, conditionally projected for 2020. By summarising the results solely at the level of the LLL concept, it can be asserted that, assuming the Strategy for ensuring LLL (2004) remains the key document for the policy on Lithuania’s education to 2012, three education policy provisions at the strategic level for the LLL concept need to be clearly defined. The questions raised for these provisions are: how is the development of an LLL system foreseen so that it will be comprehensive, integral, and cost-effective? What should be the effective characteristics of adult learning systems? What should be done to assist the citizens of Lithuania to prepare for a professional life that corresponds to the highest standards of Europe? In order to achieve vision continuity until 2020, its provisions should provide for dissolving boundaries between different areas of the social environment of an individual, strengthening the interaction of a person with nature, evermore pronounced metacognitive processes and the importance of a search for meaningfulness over the course of personal development.
Keywords: lifelong learning; adult education; mission; vision